About the Development of the Field of Culture and Art in the Present Times - Azima Usenova (Genius Publishing Group, 2022)
According to the encyclopedic dictionary of "Philosophy", the word "Culture" means (Arabic - Madinah, urban education) and the interaction of human activities reflected in nature and interactions, it is said to be a unique method. Later, through the concept of culture, the content related to civilization began to be understood. Culture is divided into material and spiritual cultures according to its essence
Keywords: Education; Art; Culture